Comparison of different protein extraction methods of rice bran protein concentrates - A. Rahim, Farah N. (Research and Technology Transfer Affairs Division,Khon Kaen University, 2022)
This study compared the protein content and yield of rice bran protein concentrates (RBPC) extracted via enzymatic and alkaline methods. Enzymatic extraction using xylanase produced RBPC containing 47.17% protein and a 19.80% protein yield. The optimal alkaline extraction conditions (pH 9, 30 °C) obtained 44.29% protein content and 21.80% protein yield. Further evaluation of alkaline extraction revealed that finer particles led to higher protein content (51.23%) and protein yield (26.85%) compared to 0.4 mm particles. Homogenization of the slurry or the addition of saline solutions did not significantly affect the protein content or yield. Rice bran protein extracted up to 72 h using 0.4 mm particle size gave the lowest protein content (5.62%) and protein yield (1.84%). The optimal alkaline extraction conditions (pH 9, 30 °C, 0.4 mm particle size, 1:4 solvent ratio, 15 min centrifuge, cloth filter, without overnight supernatant) for rice bran protein obtained extracts with a high protein content (43–51%) and yield (13–29%).